EVALUATION THE ROLE OF SUPPLEMENTATION OF VIT. D ON SOME PHYSIOLOGICAL PARAMETERS, SEMEN QUALITY IN HYPOVITAMINOSIS D MALE RABBITS INDUCED BY FUROSEMIDE - Ayat R. Sabeeh; Muna H. AL-Saeed (Basrah Journal of Veterinary Research)
This study was planned to assess the improvement effect of supplementationVit.D on adult male rabbits with hypovitaminosis D was induced by put the malerabbits in dark room un exposure to sunlight, eaten restricted food for experimentperiod and administration of furosemide drug (0.5 mg/kg.B.W.). Vitamin D treatedrabbit group was given Vitamin D. two doses (high and low doses).Thirty adult malerabbits of (1500-2000 gm) body weight were used in this study and animals weredivided into five main groups, each of 6 rabbits. Control group treated with normalsaline, second group the male rabbits put in dark room un exposure to sunlight, eatenrestricted food and treated with furosemid 0.5mg/kg B.W. I.M for 16 days, thirdgroup the male rabbits put in dark room un exposure to sunlight, eaten restricted foodand treated with 0.5 mg/Kg B.W. of furosemid I.M for 16 days +200000IU/2ml ofVit.D in every week for 1month, fourth group the male rabbits put in dark room unexposure to sunlight, eaten restricted food and treated with 0.5mg/Kg B.W.offurosemide I.M for 16 days+100000IU/1ml of Vit.D in every week for 1month, fifthgroup put the male rabbits in dark room un exposure to sunlight, eaten restricted foodand treated with both 0.5 mg/kg B.W. of furosemid I.M for 16 days + exposure tosunlight for 5 hours in day until 1 month. The taken results exposed thathypovitaminosis D is associated by a significant (P≤0.05) decrease in body weight